A methodology for assessing cyber security in Zigbee-based IoT - Vuori, Taneli (My University, 2024)
More and more devices are connected to the internet every year. The different communication protocols involved in this transition are numerous, and the rapidly evolving internet landscape forces these protocols to evolve with it or fade into obscurity. Because of this rapid evolution and the exponential growth of internet-connected devices, the cyber security features of these devices must also evolve in tandem. In this thesis a Zigbee scanning system was created for passively scanning wireless Zigbee communications via the wardriving method to gain an in-depth look into the security features of Zigbee devices from real world examples. This thesis was conducted in two parts, the first part being the theoretical background into the subject and the second part as empirical research. A system for passively scanning Zigbee devices was built and tested, and the results were analyzed. Two of the wardriving test results were dissected and analyzed in this thesis, where the latter test drive focused almost solely on the cyber security features of the scanned communications. The results were not particularly alarming, but a few deficiencies were detected. Both legislative and informative measures can and should be taken to combat the issues related to cyber security on the Internet of Things.
Keywords: Cyber security, IoT, wardriving, Zigbee